Determinación del uso de los residuos de fique provenientes del proceso de desfibrado, como sustrato para la producción de sorbitol. (2022)
In this degree work, the pretreatments that must be carried out on fique residues will be shown, the appropriate one being the steam explosion with diluted sulfuric acid, which will be removed in the form of salt by implementing a neutralization. Subsequently, they will be subjected to a physicochemical study as a bibliographic review where their viability as a substrate for the production of sorbitol by biotechnological route will be evaluated, obtaining as a result a percentage of total solids of 19.32% P/P for fique bagasse., the juice has an average of reducing sugars in glucose of 12.37 g/L, sucrose of 4.98 g/L and fructose of 18.02 g/L, with an average pH for residues of 4.33. In order to make use of these residues, it must be taken into account that fermentable sugars dont get lost in the pretreatments. With the above aspects, a sorbitol production plant will be conceptually designed using Z. mobilis as the microorganism that produces this metabolite, at the same time the costs involved will be evaluated, thus obtaining an approximate investment of USD $285,705 for direct labor. and one corresponding to USD $110,826 for indirect labor.